The Legal Consciousness of Women as Influenced by Policing of Rape Cases - Blunden, Jessica (University of the Witwatersrand, Johannesburg, 2023)
This report aims to interrogate the relationship between women and the law in South Africa and how this relationship is informed by the way in which the South African Police Service (SAPS) handles cases of rape, specifically those where the victim knows the identity of their rapist. This report argues that there is a link between South Africa’s culture of rape and violence and whether women approach the SAPS. This link is premised on various aspects, firstly, the culture informs the legal consciousness and conduct of the SAPS. Secondly, the SAPS’ conduct then informs the legal consciousness of women in South Africa. Finally, the legal consciousness of women in South Africa then determines whether they approach the SAPS. Having established the various aspects of this argument, this report offers some ideas for potential reform from both a practical and ideological perspective. The method and approach adopted in formulating the report has not involved the use of any direct research methods, but rather an analysis of the writings and research of various scholars and organisations
A research report submitted in partial fulfilment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg, 2023
Keywords: Rape Cases; Legal Consciousness; South African Police Service (SAPS); Women and the la; UCTD; SDG-16: Peace, justice and strong institutions